2002
DOI: 10.1038/sj.onc.1205662
|View full text |Cite
|
Sign up to set email alerts
|

p53 activation results in rapid dephosphorylation of the eIF4E-binding protein 4E-BP1, inhibition of ribosomal protein S6 kinase and inhibition of translation initiation

Abstract: p53 is an important regulator of cell cycle progression and apoptosis, and inactivation of p53 is associated with tumorigenesis. Although p53 exerts many of its effects through regulation of transcription, this protein is also found in association with ribosomes and several mRNAs have been identified that are translationally controlled in a p53-dependent manner. We have utilized murine erythroleukemic cells that express a temperature-sensitive p53 protein to determine whether p53 also functions at the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 75 publications
7
86
1
3
Order By: Relevance
“…Intriguingly, cytoplasmic p53 has been found to be covalently linked to 5.8S rRNA and associated with ribosomes (Fontoura et al, 1992(Fontoura et al, , 1997. p53 induction decreases protein synthesis and S6K activity (Horton et al, 2002), but translational inhibition by p53 may occur also independently of mTOR (Constantinou and Clemens, 2005). In accordance with the former finding, Feng et al (2005) found that etoposide addition to cells resulted in downregulation of S6K activity mediated by AMPK and TSC.…”
Section: Osmotic Stresssupporting
confidence: 60%
“…Intriguingly, cytoplasmic p53 has been found to be covalently linked to 5.8S rRNA and associated with ribosomes (Fontoura et al, 1992(Fontoura et al, , 1997. p53 induction decreases protein synthesis and S6K activity (Horton et al, 2002), but translational inhibition by p53 may occur also independently of mTOR (Constantinou and Clemens, 2005). In accordance with the former finding, Feng et al (2005) found that etoposide addition to cells resulted in downregulation of S6K activity mediated by AMPK and TSC.…”
Section: Osmotic Stresssupporting
confidence: 60%
“…30 Consistent with our results, using murine leukemia cells expressing a temperature-sensitive p53 or a doxycycline-inducible lung carcinoma cell line model capable of expressing p53, it has been reported that wild-type p53 activation dephosphorylates 4E-BP1 and inhibits translation initiation. 38,39 Cooperative dephosphorylation of 4E-BP1 by PI-103 and Nutlin-3 suggests that mTOR inhibition and p53 activation strongly disrupt mTOR-mediated translational control, resulting in imbalanced expression of pro-and antiapoptotic proteins and unstable mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the eIF4E inhibitory protein 4E-BP1 has been reported to act as a tumor suppressor gene product (Rousseau et al, 1996;Lynch et al, 2004). Notably, many other tumor suppressors, such as p53 and Pdcd4 (programmed cell death 4), also exert their growth inhibitory effect by modulation of translation initiation in addition to their roles as a transcriptional regulator (Horton et al, 2002;Yang et al, 2003). Thus, as with the case of p53, translational regulation should therefore be added to the various mechanisms, including Vector FLAG-DDX3 FLAG-DDX3 L43A/DQAD Relative colony number (%) Figure 9 Analysis of the tumor growth suppressive ability of DDX3 mutants.…”
Section: Ddx3 Interacts With Eif4e and Regulates Translationmentioning
confidence: 99%
“…At 24 h post-transfection, equal numbers of transfected cells underwent [ 35 S]methionine metabolic labeling as described previously (Horton et al, 2002). Determination of the amino-acid incorporation rates in the different DDX3-knockdown stable HeLa cell lines was performed similarly.…”
Section: Plasmids and Recombinant Proteinsmentioning
confidence: 99%